The Poetics of F.N. Gorenstein’s Novel "A Fly at a Drop of Tea" (Proceedings of Southern Federal University. Philology, 2018)
Elena E. Zavyalova (Astrakhan, Russian Federation)The article traces the intertextual relations of not widely studied novel by the writer-emigrant Friedrich Naumovich Gorenstein «The fly at the drop of tea» (1982) – folklore, mythological, biblical. It has been analyzed the episodes, which are endowed with characters of mystical meaning. Leading motives are revealed. The protagonist of the work has neither a name nor a surname, he is just a Man. Often found in the writer and in many ways similar to the author’s character is an intellectual, a Muscovite born somewhere in the south-west, apparently in a Ukrainian village. It is proved that the world, seen through the eyes of the protagonist, shows signs from past times and prohibitive space. Besides a healing remedy, warts, couples, dancing nymphs are mentioned twice. Reasoning about the eternal exhausting war between a man and a woman illustrates the picture seen later, depicting the deadly battle of a man in antique clothes with an Amazonian eagle. It is argued that the most important function of introducing rhyming images and events is to achieve the effect of the mutual permeability of past and present, dream and reality, fantasy and reality. The legend, placed in the center of the work, contains two dilemmas that are important to F.N. Gorenstein. The first is which religiosity to recognize as genuine: the frenzied rigorism of an ascetic, in his righteousness gone on about the demon, or the naive rapture of a sinner who sincerely extolled the beauty of the spirit? The second is what kind of love is true: based on volitional activity, personal activity – or on complete dissolution in the object of worship (love addiction)? It has been determined the main idea of this work that is the timeless essence of human existence, based on sacred love experience.Key words: F.N. Gorenstein, poetics, intertextuality, motive, refrain, myth, biblical image, legend, transformation.